2022
DOI: 10.1038/s41598-022-11040-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating CD34-positive cell count and height loss among older men

Abstract: Height loss starting in middle age is reportedly significantly associated with death due to cardiovascular disease. Impaired blood flow is the main pathology in cardiovascular disease. Hematopoietic stem cells such as CD34-positive cells play an important role in maintaining the microcirculation and preventing impaired blood flow by activating endothelial repair and angiogenesis. Therefore, circulating CD34-positive cell count could be associated with height loss. To clarify the association between circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Furthermore, a previous study with healthy individuals free from diabetes reported a significant positive association between post-challenge hyperglycemic spikes and functional arterial stiffness evaluated with the cardio-ankle vascular index (CAVI) [ 23 ]. Since insufficient endothelial repair due to a shortage of hematopoietic stem cells known as CD34-positive cells accelerates functional atherosclerosis as evaluated by CAVI [ 7 ] and a shortage of CD34-positive cells is an independent risk for height loss among men aged 60 to 69 years [ 6 ], increased functional arterial stiffness due to post-prandial hyperglycemic spikes might explain the association between eating speed and height loss among non-overweight individuals. Since hypoxia accelerates intervertebral disc degeneration [ 24 , 25 ], inadequate endothelial repair related to lower adaptability to hypoxia might play an important role in the development of intervertebral disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, a previous study with healthy individuals free from diabetes reported a significant positive association between post-challenge hyperglycemic spikes and functional arterial stiffness evaluated with the cardio-ankle vascular index (CAVI) [ 23 ]. Since insufficient endothelial repair due to a shortage of hematopoietic stem cells known as CD34-positive cells accelerates functional atherosclerosis as evaluated by CAVI [ 7 ] and a shortage of CD34-positive cells is an independent risk for height loss among men aged 60 to 69 years [ 6 ], increased functional arterial stiffness due to post-prandial hyperglycemic spikes might explain the association between eating speed and height loss among non-overweight individuals. Since hypoxia accelerates intervertebral disc degeneration [ 24 , 25 ], inadequate endothelial repair related to lower adaptability to hypoxia might play an important role in the development of intervertebral disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Since height loss starting in middle age is a significant risk factor for cardiovascular diseases [ 3 ], the present findings could help clarify some of the mechanisms underlying the association between height loss and cardiovascular disease. Insufficient endothelial repair [ 7 , 8 ], which is related to a shortage of circulating CD34-positive cells, is associated with height loss [ 6 ]. Circulating CD34-positive cell count is inversely associated with cardiovascular mortality [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Height is known to be strongly inversely associated with age because aging is a process that decreases height [ 2 , 25 , 26 ]. Aging could influence the risk of endothelial dysfunction [ 27 ].…”
Section: Discussionmentioning
confidence: 99%